Tungsten-doped Ni–Co phosphides with multiple catalytic sites as efficient electrocatalysts for overall water splitting. Issue 28 (2nd July 2019) - Lu, Shan-Shan; Zhang, Li-Ming; Dong, Yi-Wen; Zhang, Jia-Qi; Yan, Xin-Tong; Sun, De-Fan; Shang, Xiao; Chi, Jing-Qi; Chai, Yong-Ming; Dong, Bin
Abstract : The design of electrocatalysts including precious and nonprecious metals for the hydrogen evolution reaction (HER) in alkaline media remains challenging due to the sluggish reaction kinetics caused by the additional water dissociation step. Abstract : The design of electrocatalysts including precious and nonprecious metals for the hydrogen evolution reaction (HER) in alkaline media remains challenging due to the sluggish reaction kinetics caused by the additional water dissociation step. Herein, we fabricate tungsten-doped Ni–Co phosphides based on Ni foam (W-NiCoP/NF), which have multiple catalytic sites for water dissociation and H2 formation steps, respectively. Physical and electrochemical studies imply that bimetallic Ni–Co sites are responsible for water dissociation by absorbing hydroxide, while the W atoms function as binding sites for hydrogen intermediates (Had ) in the second step of the alkaline HER process. Benefiting from the moderate combination ability between W and H atoms, W sites could effectively convert Had to H2, and the synergistic effect between Ni–Co sites and W sites can accelerate the HER rate. W-NiCoP/NF exhibits a low overpotential of 29.6 mV at a current density of 10 mA cm −2 and a small Tafel slope of 38 mV dec −1, which is close to that of the Pt/C catalyst. W-NiCoP/NF also displays excellent oxygen evolution reaction (OER) performance and thus outstanding performance for overall water splitting. This work may provide a way to modulate multisite catalysts based on transition metal phosphides for wider application in other electrolysis fields.